2010
DOI: 10.1186/1471-2164-11-687
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented loss of ammonia assimilation capability in a urease-encoding bacterial mutualist

Abstract: BackgroundBlochmannia are obligately intracellular bacterial mutualists of ants of the tribe Camponotini. Blochmannia perform key nutritional functions for the host, including synthesis of several essential amino acids. We used Illumina technology to sequence the genome of Blochmannia associated with Camponotus vafer.ResultsAlthough Blochmannia vafer retains many nutritional functions, it is missing glutamine synthetase (glnA), a component of the nitrogen recycling pathway encoded by the previously sequenced B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…Blochmannia also maintains certain genes for basic cellular functions, such as biosynthesis of the nine essential amino acids (excluding Arginine), and urease cofactors and enzymes, which allows the symbiont to recycle urea nitrogen provided by the host’s excretory system [73, 75, 76]. In addition, the nutritional role of Blochmannia is not the only potential interaction with its host, as it has also maintained genes needed to contribute to the metabolism of nitrogen, sulfur and lipids [2426]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blochmannia also maintains certain genes for basic cellular functions, such as biosynthesis of the nine essential amino acids (excluding Arginine), and urease cofactors and enzymes, which allows the symbiont to recycle urea nitrogen provided by the host’s excretory system [73, 75, 76]. In addition, the nutritional role of Blochmannia is not the only potential interaction with its host, as it has also maintained genes needed to contribute to the metabolism of nitrogen, sulfur and lipids [2426]. …”
Section: Discussionmentioning
confidence: 99%
“…Blochmannia is a Proteobacteria specific to the Camponotini, which has been demonstrated to assist in providing essential amino acids to their host since their diets are defficient in nutrients as a consequence of their arboreal habitats [22, 23]. The nutritional role of Blochmannia is not the only beneficial aspect to the host, as it has been shown that Blochmannia also has the necessary genes to contribute to the metabolism of nitrogen, sulfur and lipids [2426]. In addition to Blochmannia endosymbionts, among members of the Camponotini tribe, there are other species of endosymbionts that have been documented from these hosts, including Arsenophonus spp., Cardinium hertigii , Hamiltonella defense , and Spiroplasma spp.…”
Section: Introductionmentioning
confidence: 99%
“…The dependence on host-supplied Gln has also been recently described in Blochmannia vafer , the primary endosymbiont of the ant Camponotus vafer , which contains urease but lacks both Glu dehydrogenase and Gln synthase [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the Ureaplasma spp. are some of the few bacterial species which encode a urease enzyme but lack the ability to assimilate ammonia into glutamine or glutamate (274), potentially explaining the very high intracellular ammonia concentration of these microorganisms (140).…”
Section: Ureasementioning
confidence: 99%